Financial Development and Economic Growth: The Empirical Evidence of the Southern Mediterranean Countries (SMC) - Aydi, Mohamed; Aguir, Abdelkader (International Journal of Economics and Financial Issues, 2017)
This paper analyzes empirically the links between financial development and the economic growth of the (SMC). The study is based on a VAR approach: The Johansen Tests for Cointegration and VECM models. The debate on the relation between the financial sphere and the real economic sphere was very ambiguous Some studies have shown a positive association between these two spheres while others presented the opposing view perfectly. On the basis of the data relative to the PSM, observed during period 1981-2014, we tried to show there is or not a positive relationship between the financial development and the economic growth. This relationship and increasingly intense for the role of the banking development and and refers to an innovation effort and modernization of the financial system. Keywords: Financial development, economic growth, Southern Mediterranean countries, Var approch. JEL Classifications: G10, O47